Synergistic Signal Amplification via Weak Value Amplification Effect and Sandwich Structure for Highly Sensitive and Specific Real-Time Detection of CA125 - Bei Wang; Yang Xu; Han Li; Zishuo Song; Tian Guan; Yonghong He (Biosensors)
Biomolecule detection is pivotal in disease diagnosis. In this study, we present a novel aptamer–antibody sandwich module integrated with an imaging weak measurement system to enhance the sensitivity and specificity of biomolecule detection. The feasibility of this approach is demonstrated using CA125. CA125 is a glycoprotein tumor marker widely used for ovarian cancer diagnosis and monitoring, with its level changes closely associated with disease progression. Given its clinical significance, developing highly sensitive and specific CA125 detection methods is crucial for precision medicine. The dual-recognition mechanism combines the high affinity of aptamers and the specificity of antibodies, significantly improving detection performance while utilizing antibodies for signal amplification. In the presence of CA125, the anti-CA125 aptamer immobilized on the chip surface captures the target, which is then specifically bound by the CA125 antibody, forming the aptamer–CA125–antibody complex. This interaction induces a change in the refractive index of the chip surface, which is detected by the imaging weak measurement system and ultimately manifested as a variation in light intensity in the resulting images. The method achieves the highly sensitive detection of CA125 in the 0.01 mU/mL range to 100 U/mL, with preliminary results showing a detection resolution of 3.98 μU/mL and high specificity against non-target proteins. Additionally, detecting CA125 in serum samples further validates the feasibility of the method’s applicability in complex biological matrices. The proposed method offers significant advantages, including high sensitivity, high specificity, label-free, multiplexed detection, low cost, and real-time detection, making it a promising platform for bio-molecule detection with a wide range of applications.